Identifying motivation factors of students choosing tourism and hospitality programs in Universiti Malaysia Kelantan - Khirrun An Nisa Bahaudin; Mohd Izzham Hakim Samuri; Suraya Ismail; Muhammad Amzar Abd Aziz (2021)
Thousands of students enroll in tourism and hospitality courses each year in order to pursue a career in the industry. The perception and motivation to enroll in tourism and hospitality programs in Malaysian universities by the students remain unknown. This study investigates the perception and motivation for students to enroll to tourism and hospitality courses in Universiti Malaysia Kelantan. Several motivation factors were identified in the previous literature such as social status, self – actualization, job opportunities, field attractiveness, ease of study and scholastic achievement are adopted in this study. A quantitative study using survey questionnaire was used in this study to obtain primary data. The study revealed that self-actualization and job opportunities were the main motivation factor for the students to enroll into tourism and hospitality programs in Universiti Malaysia Kelantan. The study provides several implications to the relevant stakeholder especially Malaysian Minister of Higher Education (MoHE) to emphasize the important of tourism and hospitality programs in Malaysian institution.